DEMOGRAPHIC CHARACTERISTICS OF SITE VICINITY AREA FOR PREPARATION IN WEST KALIMANTAN NPP SITE - alimah, siti; Euis Etty Alhakim; Sunarko; Kurnia Anzhar; Mudjiono (Deputi TIRBR-BPPT, 2021)
The potential risk of radioactive release to the environment and surrounding population can occur when there is a nuclear emergency, and nuclear preparedness planning is required for disaster mitigation. In preparedness planning, data is needed, one of which is demographic characteristics. Demographic information in site preparation can produce appropriate and efficient policy formulations because the number and density of the population, as well as the susceptible population, are known. The method used is secondary data collection, data verification, data processing, mapping, and analysis. This study aims to determine the demographic characteristics of the site vicinity. The study results show that the population density in 5 km radius area is 177 people/km2. In 2018, the total population was 5,199 people, the percentage of the male population was 50.3%, and the female population was 49.7%. The population aged ?20 years was 63.4%, 5-19 years old was 29.7%, and aged 0-4 was 6.9%. The projected population in 2047 is 6,523 people. The assumption is that in the event of a nuclear emergency, the emergency response considers the susceptible population. Evacuation of residents related to the emergency response can be carried out through 2 routes, namely through the South Singkawang District to the West Singkawang area, which is about 30 km from the site or through the Sungai Raya District to the Sungai Kunyit area, which is of about 26 km from the site.